Weekly tapping of rubber trees : Agronomical, physiological and economic aspects - Eschbach J M (Journal of Natural Rubber Research, 1986)
The change from full-spiral twice a week to half-spiral stimulated aims to decrease tapping intensity and increase productivity of the tapper. The best way of doing this is to decrease the tapping frequency and increase stimulation to maintain satisfactory yield per tree. This paper summarises the results obtained with weekly tapping frequency of d/6 6d/7 compared with a twice-weekly frequency of d/3 6d/7 on several clones in the Ivory Coast. In spite of increased stimulation, yields obtained were very often inferior, i.e. about 10;less than those obtained with two tappings per week. Not all clones react in the same way to a decrease in tapping intensity. Secondary characteristics such as dry rubber content, sucrose content and incidence of dry trees were better than with half-weekly tapping in spite of the number of stimulations being twice as high. From an economic view-point, weekly tapping greatly reduces the need for labour. The break-even point which depends on the market price and the cost of labour, if not already reached in the Ivory Coast on existing estates, has every chance of being so in view of the socio-economic advances in the developing countries.
Keywords: Rubber; Weekly tapping